Indicators Predictive Function to the Acceptance Criteria Used in the Preparatory Year at the University of Hail - Lahcene Abdullah Bachioua (University of Science and Technology, Yemen, 2014)
Indicators Predictive Function to the Acceptance Criteria Used in the Preparatory Year at the University of Hail Abstract: This study was to contribute to efforts towards foreseeing and evaluating indicators predictive of acceptance criteria used in the preparatory year at the University of Hail, It aims to show that the importance of foreseeing the quantitative criteria are capable of achieving the vision and objectives of the ruler of the adoption of programs in preparatory year. Also it concerns to arrange them in order of importance, using the university currently the proportion of high school acheivement and capacity grades, which are being submitted to National Center for Measurement and Evaluation, The study seeks to predict the rate of cumulative student through these independent variables (secondary, capacity, and acheivement) in order to determine the proportion of each variable interpretation of the variance in the dependent variable which is the cumulative average. The researcher used a method to predict a manner of the linear regression by correlations between key variables based on a sample of 1420 (976 males and 444 females), Where possible, the order of the variables according to their importance, and the analysis showed that the variable of gender did not have obvious importance, where the results of the correlation of the students (males and females) related with two variables test grades ranked as the first in terms where they showed together a square correlation coefficient of (0.48, 0.56). Then it has been followed -in the general secondary examination- by well valued function below the middle, where explains alone square correlation coefficient of (0.47, 0.51) and ranks second for males, third for females, Finally the skills test which has been interpreted with predecessors square correlation coefficient of (0.46, 0.55) ranked third for males and second for girls. The results proved that the correlation between the decision of mathematics first and second for girls and boys (0.78, 0.77), The results of the correlation between the decision of the English Language first and second for girls and boys ( 0.69, 0.76 ). Also the correlation between the rate of basic materials in the first chapter in mathematics , and English , and the second chapter for girls and boys (0.81, 0.83), This was the outcome of a relationship prediction rate for the transition from the first chapter of the second semester, when the male and girls students was (2.01, 2.76). The results confirmed the importance of the proportion of high school in explaining the variation in grade point average, So, it must be a focus on performance in high school and give the percentage of high school the largest share when tradeoffs in admissions, This confirms the consensus of researchers and specialists in the use of high school degree, and the degree of acceptance testing each a complement to another logically and statistically in general, despite the fact that these relations are not highly statistically significant, So, care must be taken when used in forecasting. Researcher thinks that the weakness of the degree of coherence because it is statistically difficult to put a mathematical model covers the reasons for success and predict academic performance, high school relationship rate per year at the university, and the relationship between the rate of high school, and tests capacity (equivalent average ) per year at the university.